Pre-Service Physical Education Teachers’ Acceptance of Mobile Learning Tools and Attitude Levels for Mobile Learning - Kıvanç Semiz; Ferhat Buyukkalkan (Türk Spor ve Egzersiz Dergisi)
The development and advancement of technology, new opportunities, and effective environments are being created in education, and the role of technology in education, delivered to students through computers, smartphones, or mobile devices, mainly through the Internet, is gaining momentum. With the opportunities provided by technology, students can offer differentiated learning activities according to their learning needs, preferences, and styles. In contrast, students can personalize their technological tools with the application and content they want and participate in this process in line with their learning preferences. The purpose of this study was to examine the acceptance of mobile learning tools and mobile learning attitudes of physical education teacher candidates in Turkey. A random stratified sampling method was used. According to the findings of the research; Physical education teacher candidates' attitude levels towards mobile learning are seen to be relatively higher than their acceptance levels of mobile devices. It has been observed that motivation and satisfaction variables, which are sub-factors of Attitude Towards Mobile Learning, have a high level of correlation with each other. On the other hand, it can be said that the willingness to use mobile devices mostly affects the acceptance of mobile learning tools. In general, students perceive mobile learning positively in educational environments. In this context, with the support of educational institutions, it is possible to include mobile devices in learning-teaching processes because of their advantages such as motivating, interesting and easy-to-use physical education teacher candidates, as well as supporting learning and being independent of time and space.